Regional Integration through Common Policies: A Case- Study of the Free Movement Policy in the EU and the ECOWAS - Sibiri, Hagan (Covenant University Journal of Politics and International Affairs, 2017)
This paper juxtaposes the conceptualization of the EU and ECOWAS and applies it to analyze the progress of both EU and ECOWAS integration process. The free movement policy within both the EU and ECOWAS was used as a case study. The paper basically relied and built on existing literature on the EU and ECOWAS regional integration efforts. The paper reveals that, unlike the EU that has chalked many successes in its regional integration efforts, ECOWAS has been on the reverse due to largely the political instability and bad governance that have plagued many ECOWAS countries; as well as the weakness of the national economies. The EU has delivered half a century of prosperity, peace and stability, raised the living standards within EU, and launched a free movement policy as well as a single European currency (the Euro), by contrast, the dream of ECOWAS single currency „the Eco‟ has been a mirage, the only field ECOWAS seems to rival the EU is it protocol on free movement within the ECOWAS region and the issuance of a single ECOWAS themed passport among Member countries.